The solution of mixed integral equation of the first kind using toeplitz matrix method (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this work, the existence and uniqueness of the solution of mixed integral equation (MIE) of the first kind is considered in the  L2  *C[0,T], T